Rancang Bangun Sistem Otentikasi Terpusat Berbasiskan Model Single Sign On di IT Telkom Surabaya - Kharisma Monika Dian Pertiwi; Rizky Fenaldo Maulana; Ardian Yusuf Wicaksono (Jurnal Ilmu Komputer, 2022)
IT Telkom Surabaya is one of the campuses located in Surabaya City, East Java. Currently IT Telkom Surabaya has thousands of students and hundreds of employees consisting of staff and lecturers. Along with the development of information technology, the IT Telkom Surabaya campus has many information systems that support its business processes. However, the information system has not used a single authentication system. So a user must remember the account used in each of these information systems. Therefore, in this study, researchers developed a centralized authentication system based on the Single Sign On model in the IT Telkom Surabaya campus. The purpose of this study is to integrate the authentication and authorization processes of several information systems in the IT Telkom Surabaya Campus. This Centralized Authentication System was built using SDLC (System Development Life Cycle) development with the waterfall method and was built based on web applications using HTML, CSS, Javascript, PHP, and using MySQL as a DBMS (Database management system). Testing on this system uses the black-box testing method which is used to test the functionality of the system by trying the functions and menus provided. The results of system functionality testing show that all functionality can run according to the flow.